Targeted APC Activation in Cancer Immunotherapy to Enhance the Abscopal Effect - Suek, Nathan; Campesato, Luis Felipe; Merghoub, Taha; Khalil, Danny N. (Frontiers in Immunology, 2019)
In oncology, the ‘abscopal effect’ refers to the therapeutic effect on a distant tumor resulting from the treatment of local tumor (e.g., ablation, injection, or radiation). Typically associated with radiation, the abscopal effect is thought to be mediated by a systemic antitumor immune response that is induced by two concurrent changes at the treated tumor: (1) the release of tumor antigens and (2) the exposure of damage-associated molecular patterns. Therapies that produce these changes are associated with immunogenic cell death (ICD). Some interventions have been shown to cause an abscopal effect without inducing the release of tumor antigens, suggesting that release of tumor antigens at baseline plays a significant role in mediating the abscopal effect. With tumor antigens already present, therapies that target activation of APCs alone may be sufficient to enhance the abscopal effect. Here, we discuss two therapies targeted at APC activation, TLR9 and CD40 agonists, and their use in the clinic to enhance the abscopal effect.